Written Versus Oral Assessment Are Both Equally Effective in Pharmacology ? (Bangladesh Journal of Medical Education, 2025)
Background: The undergraduate medical curriculum guidelines established by the Bangladesh Medical and Dental Council (BMDC) placed significant emphasis on assessing knowledge, skills, and attitudes in pharmacology. Currently, students are mostly assessed through written and oral assessments. However, oral assessment is resource-intensive and time-consuming while written assessment can efficiently assess a larger number of students in a shorter timeframe. Objective : This study aimed to observe the level of effectiveness of written assessment and oral assessment in evaluating learning objectives in pharmacology education for MBBS students. Methods: A formative interventional study was conducted from August 2022 to September 2023 at four medical colleges in Chattogram, Bangladesh, involving fourth year MBBS students and faculty members of pharmacology. Pharmacologists' opinions were gathered prior to the assessment, and post-assessment feedback from students and examiners were collected regarding the effectiveness of written and oral assessment methods in evaluating learning outcomes aligned with the curriculum objectives. Results: A total number of 240 students and 16 faculty members of pharmacology participated in the study. There was no significant differences found in students’ and teachers’ perceptions of written and oral assessment when evaluating objectives related to the cognitive and affective domains. However, written assessment was significantly preferred for evaluating objectives related to prescribing drug for special group and analyzing information. Teachers also favoured written assessment for evaluating objectives related to prescription writing. Examiners who conducted written assessment indicated that all objectives, except for communication with patients, could be effectively evaluated through written assessment. Oral examiners reported that certain objectives could be fully assessable by oral, while objectives related to drug history taking, ethics of prescribing and prescribing for special groups were partially assessable. Choosing safe and effective drugs and analyzing information could not be adequately evaluated through oral assessment. Conclusion: Findings of this suggest that written assessment can serve as a valid alternative to oral assessment in the pharmacology curriculum within medical education of Bangladesh. This study provides valuable insights for the BMDC, offering a cost-effective and time-saving approach to pharmacology assessment in the MBBS curriculum with adequate learning outcomes.BJME, Volume-16, Issue-01, January 2025: 26-39